Pengaruh Diversitas Gender Dewan Direksi dan Kepemilikan Saham Manajerial terhadap Tax Aggressive - Febrianti Febrianti; Herlina Helmy (Universitas Negeri Padang, 2023)
This study aims to review the extent of the influence of independent variables including gender diversity of the board of directors, managerial share ownership and corporate social responsibility on tax aggressiveness (Tax Aggressive). The population in this analysis numbered 161 companies verified by the Indonesian Stock Exchange (IDX) starting from 2014- 2018. Meanwhile, the number of research object samples totaled 36 companies engaged in the manufacturing sector and IDX verified starting from 2014-2018. The sampling technique used is purposive sampling. The research method is panel data regression through the data model in the form of cross sections. Processing research data using the help of software e-views version 8. Through the results of the research it can be seen where there is no significant influence between the gender diversity variable of the board of directors (X1) and Tax Aggressive. For variable X1 it is known that the first hypothesis t statistic value is (H1) of -0.026864 < ttable 1.972 with a probability level of 0.9786 > 0.05 which makes it possible to conclude that H1 is rejected. Meanwhile the managerial share ownership variable (X2) obtained a statistical value of -0.401682 < ttable 1.972 with a probability level of 0.6884 > 0.05 which can be taken where the second hypothesis (H2) in this analysis H2 is rejected.